Causal relations between knowledge-intensive business services and regional employment growth. Issue 2 (1st February 2018) - Brenner, Thomas; Capasso, Marco; Duschl, Matthias; Frenken, Koen; Treibich, Tania
ABSTRACT: Causal relations between knowledge-intensive business services and regional employment growth. Regional Studies . This paper studies the causal relations between regional employment growth in knowledge-intensive business services (KIBS) and overall regional employment growth using German labour-market data for 1999–2012. Adopting a recently developed technique, it uses a structural vector autoregressive model in which the causal directions between KIBS and other sectors are examined including various time lags. Results show that although regional growth has a negative short-term effect on KIBS, KIBS growth has a long-term positive effect on the whole regional economy. This confirms the claim that KIBS can play a key role in regional policies.